2007
DOI: 10.1152/ajpheart.01377.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte apoptosis in autoimmune cardiomyopathy: mediated via endoplasmic reticulum stress and exaggerated by norepinephrine

Abstract: -s. Cardiomyocyte apoptosis in autoimmune cardiomyopathy: mediated via endoplasmic reticulum stress and exaggerated by norepinephrine. Am J Physiol Heart Circ Physiol 293: H1636-H1645, 2007. First published June 1, 2007; doi:10.1152 doi:10. /ajpheart.01377.2006 suggests that the autoimmune cardiomyopathy produced by a peptide corresponding to the sequence of the second extracellular loop of the ␤ 1-adrenergic receptor (␤1-ECII) is mediated via a biologically active anti-␤ 1-ECII antibody, but the mechanism lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 45 publications
6
40
0
Order By: Relevance
“…Also, like azetidine, anti-β 1 -EC II antibody induced ER stress in cardiomyocytes via phosphorylation of CaMKII and p38 MAPK. The apoptotic effects of anti-β 1 -EC II antibody are abolished by specific inhibitors of CaMKII and p38 MAPK (17). Furthermore, we found that inhibition of caspase-12 function by siRNA led to a marked reduction of the apoptotic effect of β 1 -EC II IgG.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Also, like azetidine, anti-β 1 -EC II antibody induced ER stress in cardiomyocytes via phosphorylation of CaMKII and p38 MAPK. The apoptotic effects of anti-β 1 -EC II antibody are abolished by specific inhibitors of CaMKII and p38 MAPK (17). Furthermore, we found that inhibition of caspase-12 function by siRNA led to a marked reduction of the apoptotic effect of β 1 -EC II IgG.…”
Section: Discussionmentioning
confidence: 63%
“…The TUNEL assay was performed on paraffin-embedded myocardial tissue slides using an Apoptosis Detection System (Promega, Madison, WI), as described recently (17). The number of TUNEL-positive cells was measured by counting cells exhibiting green fluorescent nuclei at ×20 power in 10 randomly chosen fields in triplicate sections under an Olympus BX-FLA reflected light fluorescence microscope (Olympus Imaging America Corp., Melville, NY).…”
Section: Tunel Apoptosis Assaymentioning
confidence: 99%
See 3 more Smart Citations